Coinfection of severe acute respiratory syndrome coronavirus 2 and polyomavirus in a patient with coronavirus disease 2019 detected by enrichment next-generation sequencing: a case report - Gunadi; Esensi Tarian Geometri; Pramana Adhityo; Ali Zainal Abidin; Marcellus; Dyah Ayu Puspitarani; Fadila Dyah Trie Utami; Kristy Iskandar; Hendra Wibawa; Mohamad Saifudin Hakim (Journal of Medical Case Reports)
Abstract Background Severe acute respiratory syndrome coronavirus 2 was found first in Wuhan and declared a pandemic by the World Health Organization. Coinfection with other respiratory viruses may occur, complicating the diagnosis and treatment of coronavirus disease 2019 . Herein, we identified a Karolinska Institute polyomavirus Stockholm 60 present in a nasopharyngeal swab of a patient with severe acute respiratory syndrome coronavirus 2 infection using next-generation sequencing with an enrichment method. Case presentation A 24-year-old Indonesian woman was admitted to our institution due to a cough, cold, and sore throat. She had no family history of hypertension and diabetes mellitus, and she was well. Her vital signs were as follows: heart rate, 84 beats per minute; respiratory rate, 22 breaths per minute; temperature, 39 °C; and pulse oximetry, 96% on room air. She had runny nose and slightly inflamed pharynx. Her nasopharyngeal swab and real-time polymerase chain reaction were positive for the coronavirus disease 2019 nucleocapsid and open reading frame genes, with cycle threshold values of 32.33 and 33.74, respectively. Whole-genome sequencing of severe acute respiratory syndrome coronavirus 2 was performed using the Nextera DNA Flex for Enrichment using the Respiratory Virus Oligos Panel, Illumina MiSeq instruments, and Illumina MiSeq reagent v3 150 cycles (2 × 75 cycles). The full genomes were aligned to the reference genome (NC_045512.2) by the Burrow–Wheeler aligner algorithm. The whole-genome sequencing showed coinfection of Karolinska Institute polyomavirus Stockholm 60 (NC_009238.1) with an overall coverage of 3561x. The patient was given acetaminophen, vitamin C, vitamin D, and zinc for the treatment and discharged uneventfully from the hospital 4 days after admission. Then, 2 weeks after discharge, she visited the outpatient clinic without any further concerns. Conclusion This report presents a case of Karolinska Institute polyomavirus and severe acute respiratory syndrome coronavirus 2 coinfection in a patient with nonspecific clinical manifestation. Further studies with a larger sample size are mandatory to clarify the association between severe acute respiratory syndrome coronavirus 2 and Karolinska Institute polyomavirus coinfection, particularly on patient outcomes. Moreover, the results propose the usefulness of enrichment-based next-generation sequencing in detecting viral coinfection in patients with severe acute respiratory syndrome coronavirus 2.